KETURIŲ ELEMENTŲ METAFIZIŠKUMAS ARISTOTELIO FIZIKOJE. - Čiurlionis, Jonas (Problems / Problemos, 2017)
The article analyzes a problem of four elements in Aristotle's physics. It is claimed that elements are grounded metaphysically as first substances and manifestations of matter. Most of the time analysis of Aristotle's philosophy draws attention to form as substance. The article reveals that despite the importance of form in a physical world of generation and corruption primary substances that defy the material Being cannot be ignored. Thus four elements are "embodiment" of prime matter. It is shown that the system of four elements, while serving as the basis to physics, at the same time is inseparable from the general Aristotelian philosophical system. Great importance is given to the issue of opposites, which form the essential physical system of first principles.